2017
DOI: 10.2337/db17-0046
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Regulation of Insulin Sensitivity by Dietary Lipid Versus Carbohydrate Excess

Abstract: To understand the mechanisms in lipid-induced insulin resistance, a more physiological approach is to enhance fatty acid (FA) availability through the diet. Nine healthy men ingested two hypercaloric diets (in 75% excess of habitual caloric intake) for 3 days, enriched in unsaturated FA (78 energy % [E%] fat) (UNSAT) or carbohydrates (80 E% carbohydrate) (CHO) as well as a eucaloric control diet (CON). Compared with CON, the UNSAT diet reduced whole-body and leg glucose disposal during a hyperinsulinemic-eugly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 52 publications
6
50
0
1
Order By: Relevance
“…Muscle sn ‐1,3 DAG and IMTG content for the Unsat group has been previously published by Lundsgaard et al . (17).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Muscle sn ‐1,3 DAG and IMTG content for the Unsat group has been previously published by Lundsgaard et al . (17).…”
Section: Resultsmentioning
confidence: 99%
“…This is congruent with an accumulating body of evidence (4650) suggesting that acutely augmented availability of circulating lipids does not inhibit insulin‐stimulated muscle glucose uptake by regulation at the proximal part of the canonical insulin signaling. We recently demonstrated that consumption of a hypercaloric HFD enriched in Unsats for 3 d increased FA oxidation and inhibited muscle pyruvate dehydrogenase phosphoregulation, resulting in accumulation of glucose‐6‐phosphate content compared to the Con diet (17). This diet‐induced inhibition of pyruvate dehydrogenase correlated to the reduced insulin‐stimulated glucose uptake in muscle (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, it was recently reported that 3 days of excessive dietary fat intake reduced insulin‐stimulated leg glucose uptake without changes in skeletal muscle signalling (Lundsgaard et al . ). This is very similar to our own observations, where 7 days on a HFHC diet resulted in reduced postprandial glycaemic control that was attributable to reduced glucose clearance (determined using dual‐glucose tracers during an oral glucose challenge) despite maintained skeletal muscle insulin signalling (Parry et al .…”
Section: Introductionmentioning
confidence: 97%